1987
DOI: 10.1007/bf03259876
|View full text |Cite
|
Sign up to set email alerts
|

Flumazenil in Benzodiazepine Antagonism

Abstract: In anaesthesia and in the intensive care unit, benzodiazepines have proven safe and effective agents for the induction and maintenance of sedation for a variety of therapeutic goals. However, in these contexts, or in benzodiazepine overdose, it is often desirable to be able to terminate or interrupt sedation without waiting for the effect of the benzodiazepine to become dissipated by normal metabolism and excretion. Flumazenil, a 1,4-imidazobenzodiazepine, is a highly effective, specific benzodiazepine antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…The dose of flumazenil used in the present study was derived from existing results of pharmacological and toxicological studies of the drug [17,34]. Several authors have reported that patients with pure benzodiazepines overdose require <1 mg flumazenil to fully reverse benzodiazepine-induced coma [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The dose of flumazenil used in the present study was derived from existing results of pharmacological and toxicological studies of the drug [17,34]. Several authors have reported that patients with pure benzodiazepines overdose require <1 mg flumazenil to fully reverse benzodiazepine-induced coma [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Flumazenil is well known as a benzodiazepine antagonist with the potential to bind with gamma-aminobutyric acid receptors. 73 Few studies have reported the GABA-A upregulation and augmented tone of GABAergic tone in patients with HE. 74,75 Upregulation of GABAergic neurons performs a vital role in the alteration of J o u r n a l P r e -p r o o f 9 neurocognitive outcomes in patients with HE.…”
Section: Flumazenilmentioning
confidence: 99%
“…Flumazenil is a competitive antagonist of benzodiazepines binding to gamma aminobutyric acid (GABA)-A receptor. 69 Because GABAergic neurons up-regulation has been suggested to be involved in pathogenesis of HE, flumazenil can be used as a potential treatment for HE. 70 In a meta-analysis including 12 trials with 842 patients, flumazenil had a beneficial effect on HE (RR, 0.75; 95% CI, 0.71-0.80), with no significant difference in serious adverse events as compared with placebo.…”
Section: August 2022mentioning
confidence: 99%